Music therapy for young children who have special needs : the music therapy experience from the perspectives of carers and professionals : thesis in partial fulfilment of the requirements of the degree of Master of Music Therapy at the New Zealand School of Music, Wellington, New Zealand - Chiang, Jenny Yu Kuan (Massey University, 2008)
This project aims to investigate how carers and other professionals perceive the music therapy process over time. Music therapy has been used to address a wide range of diagnoses and developmental issues of young children. The research was conducted during my clinical placement working with young children who have been referred to a child development team. The participants in this project were carers with children with special needs. The children were diagnosed with various disabilities and required different support and developmental goals. Each child attended individual music therapy sessions once a week over a period of three to nine months. It was speculated that many other changes or developmental progress could occur along with the goals and objectives set by me in the music therapy process. To understand fully what other changes or progress the children have made with the input of music therapy, the research was designed using open-ended interviews to find out what the carers and a professional witnessed during and in between the sessions. Three carers were involved in a one-on-one in-depth interview in which they were encouraged to talk about their observation and perception of music therapy. A speech-language therapist was also invited to participate in an in-depth interview. Data derived from the interviews was analysed using a thematic analysis approach. The findings compare themes generated from the clinical notes and interview data. The results showed some shared experiences amongst the participants as well as exceptions influenced by parental differences and the children’s conditions. Examination of the similarities and differences between the clinical notes and the interview data helped me validate the outcome of music therapy intervention and gain more insights into effective practice.
Keywords: Music therapy; Children with disabilities; Disabled children; Fields of Research::410000 The Arts::410100 Performing Arts Studies::410101 Music studies